Application radio frequency in keeping track of shopping trolley [electronic resource] - Muhammad Muinuddin Mat Jusoh, 1987- , author; Harun Ismail, supervisor (2011)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik - Elektronik)) - Universiti Teknologi Malaysia, 2011